Picturesque Trinidad - (:unkn) unknown (My University, 2011)
A small house nestles amoung the trees along the shoreline.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coasts--Trinidad and Tobago; Trees--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Dwellings--Trinidad and Tobago; [1911]